Akmaluddın Al-Nahjuwanı dan Kıtab Syarḥu al-Isyārāt - Akhmad Rofii Damyati (Tasfiyah: Jurnal Pemikiran Islam, 2018)
In the history of philosophy, Peripatetic has been acknowledged as the most influential philosophy school.  Even, in Islamic thought tradition, this Aristotelian school of philosophy has significant influence. Among Masysya’i philosophers, i.e. Peripatetic adherents in Islam, Ibn Sina is the most renowned Islamic philosopher who arduously develops Aristotelian thoughts. He is not only to copy Aristotle, instead inventing new thoughts in philosophy. Al-Isyarat wa al-tanbihat is one of vaunted Ibn Sina’s works. It becomes that last work before his passing away. This book contains the philosophy works he wrote beforehand. In the history of Islamic thought history, especially after 12th century, this work has significant and strong influence in Moslem philosophers. Nonetheless, many Moslem philosophers, both who support or reject him, commented (Syaraḥ) this book. These comments (syurūḥ) are then followed with some annotative elaborations like hasyiyah, ta’liq, muhakamat, etc. While the precious values of this book are beyond question, some commentaries and annotative works remain difficult to get since most of them kept in the form of manuscripts in various large libraries around the world. One of significant and rare manuscripts is that of Syarḥ al-Isyārāt wa al-Tanbīhāt written by Akmaluddin Al-Nahjuwani. This writing aims to introduce Akmuluddin al-Nahjuwani in his work titled Syarḥu al-Isyārāt and analyze its contents in brief.Ibn Sina, The Tradition of Isyārāt wa al-Tanbīhāt, Akmaluddin al-Nahjuwani, Syarḥu al-Isyārāt.